Pola Hubungan Relasionalitas Antara Hukum Islam, Adat Dan Nasional Perspektif Filsafat Ilmu Dan Hukum: The Relational Pattern Between Islamic Law, Customary Law, and National Law from the Perspective of Philosophy of Science and Law - Aditya Setiawan; Jibran Hafidz; Roibin Roibin (Institut Agama Islam Negeri Fattahul Muluk Papua, 2026)
This study aims to analyze the relational pattern between Islamic law, customary law, and national law in Indonesia from the perspective of philosophy of science and law. This research uses a normative method with a conceptual approach, through the examination of legal documents, statutory regulations, literature, and relevant court decisions. The research materials consist of primary legal materials in the form of books and journals on Islamic law, customary law, and national law, as well as secondary materials in the form of legal dictionaries and encyclopedias. The analysis is conducted descriptively and analytically through the stages of editing, classification, verification, analysis, and drawing conclusions. The results of the study show that Islamic law, customary law, and national law are complementary, harmonious, and responsive to the dynamics of society. Islamic law provides a sharia basis, customary law is flexible and contextual, while national law integrates the principles of Pancasila and the 1945 Constitution. The relationship among the three includes ontological, epistemological, and axiological dimensions, thereby forming a national legal system that is fair, contextual, and socially just. The conclusion of this study emphasizes the need for a flexible, normative, and interconnected model of legal relations, with the strengthening of dispute resolution institutions based on local wisdom to effectively support legal pluralism.